For a sound fiscal policy: Enabling public investment - Hubertus Bardt; Sebastian Dullien; Michael Hüther; Katja Rietzler (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2020)
Public investment has been badly neglected in Germany over the past two decades, with the result that the public capital stock no longer meets the standards of a modern economy and is inadequate for the challenges that will be posed by demographic change and Germany's international decarbonisation commitments. - In total, the areas of education, transport, communication networks and decarbonisation will require at least an additional exteuro450 billion of public investment or public investment subsidies over the next 10 years, equivalent to approximately exteuro45 billion a year. - While this amount is manageable in overall economic terms, it is unrealistic to suggest that the required investment can be financed entirely through the reallocation of existing funds within the budget. Consequently, the German Constitution's debt rules should be supplemented by a Golden Rule allowing for borrowing equivalent to the value of the net investment. The leeway offered by mechanisms such as off-budget entities should be utilised until such a rule has been implemented. A sustained reduction in local government debt will also be important in view of the key role played by the municipalities in public investment, especially in transport infrastructure. – – Die öffentliche Hand in Deutschland hat in den vergangenen beiden Jahrzehnten die eigenen Investitionen massiv vernachlässigt. Das Ergebnis ist ein öffentlicher Kapitalstock, der den Anforderungen einer modernen Volkswirtschaft nicht gerecht wird und unzureichend ist, um den Herausforderungen der durch den anstehenden demografischen Wandel und der - international zugesagten - Dekarbonisierung zu begegnen. Rechnet man die Erfordernisse in den Bereichen Bildung, Verkehr, Kommunikationsnetze und Dekarbonisierung zusammen, so kommt man auf zusätzlich notwendige rund 450 Mrd. Euro ? an öffentlichen Investitionen oder öffentlicher Investitionsförderung über die kommenden 10 Jahre, also rund 45 Mrd. Euro ? pro Jahr. Diese Summe ist volkswirtschaftlich gut zu schultern. Es ist aber unrealistisch, diese Investitionen allein durch Umschichtung in den bestehenden Haushalten zu finanzieren. Deshalb sollten die Schuldenregeln im Grundgesetz um eine goldene Regel erweitert werden, die eine Kreditaufnahme im Umfang der Nettoinvestitionen erlaubt. Bis zur Umsetzung einer solchen Regel sollten Spielräume, etwa durch Extrahaushalte, genutzt werden. Wichtig ist darüber hinaus eine nachhaltige Entschuldung der Kommunen, die eine zentrale Rolle für öffentliche Investitionen, insbesondere bei der Verkehrsinfrastruktur spielen.
Keywords: 330; Öffentliche Investition; Infrastrukturinvestition; Investitionspolitik; Haushaltskonsolidierung; Reform; Deutschland